SOME DETAILS OF FOREST FIRE STATISTICS IN BRAZIL - Soares1, Ronaldo Viana; Santos, Juliana Ferreira; Batista, Antonio Carlos (Floresta, 2009)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} p.MsoFootnoteText, li.MsoFootnoteText, div.MsoFootnoteText {mso-style-noshow:yes; mso-style-link:" Char Char"; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US;} span.CharChar {mso-style-name:" Char Char"; mso-style-noshow:yes; mso-style-locked:yes; mso-style-link:"Texto de nota de rodapé"; mso-ansi-language:EN-US; mso-fareast-language:PT-BR; mso-bidi-language:AR-SA;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> <!--[if !mso]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> <!--[if !mso]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The objective of this research was to answer some questions about forest fire occurrence in Brazil. A total of 19,377 fires were analyzed in the period 1998 – 2002. Tabulated data, in percentage, were transformed through<!--[if gte vml 1]> <![endif]--><!--[if !vml]--> <!--[endif]--><!--[if gte mso 9]> <![endif]-->and then submitted to the analysis of variance. The means were compared through the SNK test at 5% significance level. Results showed significant differences both, in number of fires and burned areas along the months of the year. August was the month with higher number of fires, followed by July, October and September; August, September and November presented the highest burned areas. Significant differences were also detected among the group causes and along the daily hours. Incendiary was the leading cause, statistically different from the other groups, both in number of fires and burned area. About 69% of the fires, corresponding to 66% of the burned area occurred between 12 noon to 6:00 PM. Number of fires starting hourly, from 1:00 PM to 4:00 PM, didn’t differ statistically among them, but were significantly different from the other daily hours. As for the burned areas, fires starting at 5:00 PM should be included in the previous group. No statistical difference was detected among the days of the week both, for the number of fires and the burned areas, showing that, on the contrary of the popular belief, fires don’t preferentially occur during the weekends.